Beyond Neoliberal Imposition: State–Local Cooperation and the Blending of Social and Economic Objectives in French Urban Development Corporations. Issue 2 (2nd April 2016) - Pinson, Gilles; Morel Journel, Christelle
Abstract: For more than 15 years, the French central State created Etablissements publics d'aménagement in a series of major cities. These EPAs are in charge of large urban development projects mixing infrastructure, office development and housing projects and have been given formal authority over land use regulation. The similarities between French EPAs and British Urban Development Corporations created in the 1980s are striking. In many ways, the case of the EPA fits with the neoliberalization framework provided by radical geographers. Nevertheless, this case also shows limits to the generalization of this theoretical framework. Firstly, the distinction between two clearly distinct periods characterized by different agendas, policy instruments and systems of relations between actors and levels is far from convincing in the French case. Secondly, evolutions that could be attributed to neoliberal urbanism are rather the result of processes of rationalization within organizations or professions which may have little to do with neoliberalism, or the result of a transformation of the welfare State and the reassessment of ways of producing social justice. On this basis, we argue for theoretical frameworks that put neoliberalization at its right place and allow its articulation with other trends of change such as rationalization and the refinement of Welfare mechanisms.